2016
DOI: 10.1186/s12931-016-0409-5
|View full text |Cite
|
Sign up to set email alerts
|

Lung-specific RNA interference of coupling factor 6, a novel peptide, attenuates pulmonary arterial hypertension in rats

Abstract: BackgroundPulmonary arterial hypertension (PAH) is a progressive and life-threatening disease associated with high morbidity and mortality rates. However, the exact regulatory mechanism of PAH is unknown. Although coupling factor 6 (CF6) is known to function as a repressor, its role in PAH has not been explored. Here, we investigated the involvement of endogenous CF6 in the development of PAH.MethodsPAH was induced with monocrotaline (MCT), as demonstrated by significant increases in pulmonary artery pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The poor prognosis of patients afflicted by this disease despite treatment with currently available vasodilator drugs makes the development of new treatment strategies imperative. If vascular remodelling can be developed from redundant mediators, a combination “cocktail” consisting of anti-remodelling agents such as endothelin inhibitors, prostacyclin, and anti-inflammatory agents such as A-740003 may be more beneficial for patients with PAH than any single agent alone [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The poor prognosis of patients afflicted by this disease despite treatment with currently available vasodilator drugs makes the development of new treatment strategies imperative. If vascular remodelling can be developed from redundant mediators, a combination “cocktail” consisting of anti-remodelling agents such as endothelin inhibitors, prostacyclin, and anti-inflammatory agents such as A-740003 may be more beneficial for patients with PAH than any single agent alone [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the levels of CF6 have been shown to markedly increase in rats with lung disease [ 11 , 12 ]. Our previous experiments have also demonstrated that CF6 was increased in monocrotaline (MCT)-induced PAH and that the inhibition of CF6 alleviated PA remodeling in rats [ 13 ]. These results demonstrated the critical role of CF6 in the pathogenesis of MCT-PAH.…”
Section: Introductionmentioning
confidence: 99%